(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
To date, among the problems of modern dentistry, one of the important places is occupied by periodontal disease. Numerous scientists and practicing doctors note the medical and social significance of the problem under consideration. Modern aspects of the etiology and pathogenesis of chronic periodontitis remains a little studied issue. The results of the analysis of literature data on chronic periodontitis are presented.